2016
DOI: 10.1590/s1980-6574201600040008
|View full text |Cite
|
Sign up to set email alerts
|

Neuromuscular control strategies of the trunk antagonist muscles during the Biering-Sorensen test in individuals with recurrent low back pain and healthy subjects

Abstract: To compare the activation pattern of the trunk antagonistic muscles and also the myoelectric manifestations of muscle fatigue between subjects with and without recurrent non-specific low back pain, during the fatigue provocation of the erector spinae. Methods: The study involved 19 subjects with recurrent low back pain with a non-specific cause (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 27 publications
0
5
0
1
Order By: Relevance
“…In this study we observed that for the two walking conditions, there are different activation standards, and with the speed increase, the activation increase of all the muscles of the evaluated trunk (IO, MUL, LIC, EO, and AR). We believed that on performing walks at low speed, there is higher temporal variability in exchange of higher dynamic stability [13]. This way, on increasing the speed and instability, the muscles EO, IO, and AR increase the activation producing higher muscular strength and consequently increasing the rigidity of the trunk muscles and, therefore, increasing the stability [27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study we observed that for the two walking conditions, there are different activation standards, and with the speed increase, the activation increase of all the muscles of the evaluated trunk (IO, MUL, LIC, EO, and AR). We believed that on performing walks at low speed, there is higher temporal variability in exchange of higher dynamic stability [13]. This way, on increasing the speed and instability, the muscles EO, IO, and AR increase the activation producing higher muscular strength and consequently increasing the rigidity of the trunk muscles and, therefore, increasing the stability [27].…”
Section: Discussionmentioning
confidence: 99%
“…Thirty-four sedentary women attended the survey, aging from 18 to 27 years old; from which 18 composed the chronic lumbar pain team (LPT) and 16 composed the control team (CT), see Table 1. The criteria for LPT eligibility were to be female, sedentary for at least six months, with at least two idiopathic episodes of lumbar region pain in the last three months [13]. The inclusion criteria were the same for WLP; however, the participants should not have presented episodes of lumbar pain in the last three months.…”
Section: Participantsmentioning
confidence: 99%
“…23 were also applied. All evaluations were repeated after the two months of Pilates, respecting a maximum period of one week before and after the protocol for conducting the evaluations and in all meetings before and after the Pilates the visual analog scale of pain (VAS) 24 was conducted.…”
Section: Subjectsmentioning
confidence: 99%
“…Os critérios de inclusão para o GDL foram: mulheres, sedentárias por no mínimo 6 meses, que apresentavam pelo menos dois episódios de dor em região lombar nos últimos 3 meses e que não estava relacionada a nenhuma causa aparente. Para o GSDL os critérios de inclusão eram mulheres, sedentárias por no mínimo 6 meses e que não tiveram nenhum episódio de dor lombar no último ano 12 .…”
Section: Sujeitosunclassified